Impact of adoption of heat-stress tolerant maize hybrid on yield and profitability: Evidence from Terai region of Nepal - Kulkarni, Atul P.; Tripathi, Mahendra P.; Gautam, Damodar; Koirala, Keshab B.; Kandel, Manoj; Regmi, Dhruba; Sapkota, Sudha; Zaidi, Pervez Haider (Frontiers in Sustainable Food Systems, 2023)
Abiotic stresses (drought, heat) are one of the major impediments to enhancing the maize productivity of marginal farmers in the facet of climate change. The present study attempts to investigate the impact of heat-tolerant maize hybrid on yield and income in the Terai region of Nepal. This study uses cross-sectional farm household-level data collected in August 2021 from a randomly selected sample of 404 rural households. We used a doubly robust inverse probability weighted regression adjustment method to obtain reliable impact estimates. Adoption of heat-tolerant hybrid increases yields by 16% and income by 44% in the spring season (a stress condition). Overall, yield increases by 12%, net income by 31%, saving of 40% in seed costs, and per capita food expenditure increases by 8.50%. Hence a conducive environment must be created for scaling up heat-tolerant maize varieties to increase productivity, minimize risk, and transform of the maize sector.